2015
DOI: 10.1007/s11357-015-9797-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between telomere length and beekeeping among Malaysians

Abstract: The belief that beekeepers live longer than anyone else is present since ages. However, no research has been done to explore the longevity of life in beekeepers. Here, we investigated the telomere length in 30 male beekeepers and 30 male non-beekeepers and associated them with the longevity of life using Southern analysis of terminal restriction fragments (TRFs) generated by Hinf I/Rsa I digestion of human genomic DNA using TeloTAGGG Telomere Length Assay. Interestingly, we found that the telomere length of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Royal jelly prevents the entry into senescence of different cell groups [75]. Regular consumption of beehive products such as honey, pollen, and propolis reduces the speed with which telomere shortening occurs [76].…”
Section: Mechanisms Of Honey and Pollen In Oamentioning
confidence: 99%
“…Royal jelly prevents the entry into senescence of different cell groups [75]. Regular consumption of beehive products such as honey, pollen, and propolis reduces the speed with which telomere shortening occurs [76].…”
Section: Mechanisms Of Honey and Pollen In Oamentioning
confidence: 99%
“…The results proved the leading effect of honey bee. Nasir et al (2015) in Malaysia tested honey effect on telomerase enzyme by checking the telomeres length in bee keepers who consume honey for long time periods, which showed the longer telomeres length in the bee keepers is associated with the longer period of honey consumption that confirmed the positive effect of honey on telomeres length and telomerase enzyme. El-Kased et al (2017) in Egypt reported that 75% honeychitosan hydrogel possesses greater wound healing activity compared to commercial ones and safely used as an effective natural topical wound healing treatment Jenkhetkan et al (2017) tested the effect of royal gel on telomerase activity, and showed that treating the cells by royal gel at low doses caused maximum benefits.…”
Section: Introductionmentioning
confidence: 87%
“…Lifestyle stress and environmental factors, such as diet, can influence telomere length [ 140 ]. The results of research involving human subjects showed that prolonged and frequent intake of bee products, including propolis, is linked to telomere length [ 141 ]. In Nasir et al’s (2015) study, which involved comparing beekeepers consuming bee products with non-beekeeper control subjects abstaining from bee products and beekeeping-related activities, it was observed that annual bee product consumption correlated with an average increase of 0.258 kbp in telomere length [ 141 ].…”
Section: Telomere Lengthmentioning
confidence: 99%
“…The results of research involving human subjects showed that prolonged and frequent intake of bee products, including propolis, is linked to telomere length [ 141 ]. In Nasir et al’s (2015) study, which involved comparing beekeepers consuming bee products with non-beekeeper control subjects abstaining from bee products and beekeeping-related activities, it was observed that annual bee product consumption correlated with an average increase of 0.258 kbp in telomere length [ 141 ]. The results also revealed that a greater daily frequency of bee product intake was associated with an average increment of 2.66 kbp in telomere length [ 141 ].…”
Section: Telomere Lengthmentioning
confidence: 99%